Foreign direct investment and macroeconomic determinants: some empirical result / Nor’ Azurah Md Kamdari, Raudzah Roslan and Muhd Kamil Ibrahim - Md Kamdari, Nor’ Azurah; Roslan, Raudzah; Ibrahim, Muhd Kamil (Faculty of Administrative Science and Policy Studies, 2012)
Malaysia has been one of the most successful Southeast Asian countries in attracting Foreign Direct Investment. It has always endeavored to maintain the competitiveness of FDI determinants like legal infrastructure. Many policy instruments have been set up. The Malaysian government has improved the value of the present determinants and is considering new strategies to attract FDI. This paper uses time series data to indentify macroeconomic variable in influencing foreign direct investment in Malaysia. There were four variable influences the inflow foreign direct investment in Malaysia which is, gross domestic product, growth rate of GDP, trade deficit and inflation rate. The main finding from the time series data is there is significant relationship between macroeconomic variable with foreign direct investment in Malaysia. In other word the inflow foreign direct investment is increase when our country is good in economic conditions.